IMPLEMENTASI PENYULUHAN PEMINTAL BENANG SUTERA ALAM DALAM UPAYA PEMBERDAYAAN UMKM MISRO TENUN TANJUNG - Rumiasih, Rumiasih; Susanti, Eka; ,S.T.,M.Kom., Sarjana; Tussa'ddiyah, Ra Halimah; Fajriansyah, Muhammad Mizan; Azhariah, Rahmadiani (Jurnal Likhitaprajna, 2025)
The natural silk industry represents a potential creative economy sector managed by MSMEs in Indonesia, particularly in the Palembang weaving craft sector. However, the silk thread spinning process is still largely manual, which is time-consuming, results in inconsistent thread quality, and impacts low artisan productivity. To address these challenges, this community service activity implemented an Internet of Things (IoT)-based innovation by designing an automatic silk thread spinning machine. The system was designed using an ESP32 microcontroller, a DC motor, a BTS7960 driver, and the Blynk application for remote monitoring and control.The implementation method included identifying partner issues, designing and building a prototype, testing functionality, and providing outreach and training to the Misro Tenun Tanjung MSME. The implementation results demonstrated that the machine operated stably, increased production efficiency, and produced more uniform thread quality compared to manual methods. Furthermore, artisans benefited from the transfer of technological knowledge, improved digital skills, and the opportunity to expand production capacity without compromising local cultural values.This activity not only provides technical solutions but also serves as a means of community empowerment through collaboration between academics and MSMEs. Thus, the IoT-based yarn spinning innovation has the potential to support the sustainability of tradition-based creative industries, while simultaneously making Palembang's weaving craft more competitive in facing the challenges of the global creative industry.